Developing and Evaluating a Cloud Service Relationship Theory - Huntgeburth, Jan (Progress in IS,, 2015)
This book develops, evaluates and refines a cloud service relationship theory that explains how cloud users' uncertainties arise in these relationships and how they can be mitigated. To that end, the book employs principal-agent theory and the concepts of bounded rationality and social embeddedness. Beyond advancing IS research, the findings presented can greatly benefit governments, IT departments and IT providers, helping them to better understand cloud service relationships and to adjust their cloud service strategies accordingly.